Electromagnetic shielding aerogel with double-layer structure and preparation method thereof
By adopting a double-layer structure electromagnetic shielding aerogel, using the combination of cellulose nanofibers, hollow cobalt nickel carbon nanocages and small-layer MXene, the problem of difficult electromagnetic shielding materials to achieve poor environmental protection performance is solved, and the existing electromagnetic shielding materials are realized. It has excellent low reflection characteristics and heterogeneous photothermal conversion performance, and is suitable for lightweight multi-function electromagnetic shielding composite materials and special electromagnetic protection facilities.
Patent Information
- Application Number
- CN202411560245.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing electromagnetic shielding materials are mainly reflection, and it is difficult to achieve electromagnetic stealth function, and there are problems with poor environmental protection performance, making them difficult to apply in lightweight multi-function electromagnetic shielding composite materials and special electromagnetic protection facilities.
Using an electromagnetic shielded aerogel with a double-layer structure, it is composed of cellulose nanofibers, hollow cobalt nickel carbon nanocages and a small layer of MXene. Through the design of the double-layer structure, incident electromagnetic waves occur multiple times between the absorbing layer and the reflecting layer. Scattering and reflection to achieve electromagnetic invisibility effect.
It achieves excellent low reflection characteristics of gigahertz electromagnetic shielding performance, has good heterogeneous photothermal conversion performance, low density and good stability, and is suitable for lightweight multifunctional electromagnetic shielding composite materials and special electromagnetic protection facilities. field.
Smart Images

Figure CN119427861A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials, and specifically, relates to an electromagnetic shielding aerogel with a double-layer structure and a preparation method thereof. The electromagnetic shielding aerogel prepared by the method not only has excellent low-reflection characteristics of gigahertz electromagnetic shielding efficiency, but also has excellent heterogeneous photothermal conversion performance, and has great application potential in the fields of lightweight multifunctional electromagnetic shielding composite materials, special electromagnetic protection facilities, electromagnetic stealth materials, and electronic equipment resistant to harsh environments. Background Art
[0002] Electromagnetic shielding materials are a type of material that can be used to absorb or reflect electromagnetic waves. They can not only be used to prevent electronic equipment from operating abnormally due to electromagnetic interference, but also to prevent diseases caused by the thermal effects of electromagnetic radiation in the human body. In recent years, more and more researchers have designed and prepared a variety of electromagnetic shielding materials to shield electromagnetic waves. For example, Zhang et al. proposed to use electron beam evaporation to load vertical copper and nickel on graphene nanowalls, and successfully prepared a thin film composite with electromagnetic shielding effect (JZ Zhang, HLShen, ZH Wang, TR Wu, Carbon. 2024, 225, 119144); Guo et al. used Cu and Ni to modify the matrix film, and prepared a new type of electromagnetic shielding material by chemical plating and casting (BZ Guo, JY Liang, JFChen, Y. Zhao, RSC Adv., 2022, 12, 29688-29696); Wang et al. proposed to use the electrodeposition method to prepare a composite film with electromagnetic shielding effect by compounding Bi2Te3 and carbon cloth (X. Wang, TF Shi, CL Wan, P A Zong, ZG Liu, W. Huang, Carbon, 2023, 213, 118298); These electromagnetic shielding materials have good electromagnetic shielding capabilities, but their application range is limited due to their high density and easy corrosion. Shahzad et al. prepared a highly conductive electromagnetic shielding film composed of a new type of two-dimensional material MXene obtained by acid etching, which achieved excellent electromagnetic shielding performance under the premise of corrosion resistance and low density. (F. Shahzad, Bi2Te3 M. Alhabeb, CB Hatter, B. Anasori, SM Hong, CMKoo, Y. Gogotsi, Science, 2016, 353, 1137-1140)
[0003] However, the above electromagnetic shielding materials have an electromagnetic loss mechanism mainly based on reflection, which makes it difficult to achieve electromagnetic stealth function, and the electromagnetic waves reflected back into free space are prone to secondary electromagnetic pollution, and have poor environmental performance. With the increasing demand for electromagnetic shielding materials in today's society, it is difficult to apply them to some lightweight multifunctional electromagnetic shielding composite materials with special low-reflection requirements, special electromagnetic protection facilities, and electronic equipment resistant to harsh environments. Therefore, it is still necessary to develop an electromagnetic shielding material with multifunctional low-reflection characteristics to further improve its application value. Summary of the invention
[0004] In response to the problems of traditional methods, according to one aspect of the present invention, one purpose of the present invention is to provide an electromagnetic shielding aerogel with a double-layer structure, which not only has excellent shielding capability with low reflection characteristics, but also has certain photothermal conversion capability, low density and the possibility of large-scale production, and has great application potential in the fields of lightweight multifunctional electromagnetic shielding composite materials, special electromagnetic protection facilities, electromagnetic stealth materials and electronic equipment resistant to harsh environments.
[0005] Disclosed is an electromagnetic shielding aerogel with a double-layer structure, which is composed of cellulose nanofibers, hollow cobalt-nickel-carbon nanocages and a few-layer MXene. The electromagnetic shielding aerogel has a double-layer structure, wherein the first layer is composed of cellulose nanofibers and hollow cobalt-nickel-carbon nanocages, and the second layer is composed of cellulose nanofibers and a few-layer MXene.
[0006] Preferably, in the electromagnetic shielding aerogel according to the present invention, the weight content of the hollow cobalt-nickel-carbon nanocage in the first layer and the few-layer MXene in the second layer are the same or different, and preferably the same.
[0007] Preferably, the cellulose nanofiber content in the first layer and the second layer of the electromagnetic shielding aerogel according to the present invention is the same.
[0008] Preferably, the electromagnetic shielding aerogel with a double-layer structure according to the present invention is characterized in that in the electromagnetic shielding aerogel, the weight ratio of the few-layer MXene and the hollow cobalt-nickel-carbon nanocage is 0.1:1 to 10:1, more preferably 0.3:1 to 3:1, and even more preferably 1:1.
[0009] Preferably, in the electromagnetic shielding aerogel according to the present invention, the weight ratio of the few-layer MXene powder to the cellulose nanofiber is 0.1:1 to 1:1; preferably 0.25:1 to 0.75:1, and further preferably 0.5:1.
[0010] Preferably, in the electromagnetic shielding aerogel according to the present invention, the weight ratio of the hollow cobalt nickel carbon nanocage to the cellulose nanofiber is 0.1:1 to 1:1; preferably 0.25:1 to 0.75:1, and further preferably 0.5:1.
[0011] According to another aspect of the present invention, an object of the present invention is to provide a method for preparing an electromagnetic shielding aerogel having a double-layer structure, comprising the following steps:
[0012] 1) Preparation of hollow cobalt-nickel-carbon nanocages
[0013] Under stirring conditions, 6 parts by weight of zinc nitrate hexahydrate and 6 parts by weight of 2-methylimidazole are added to 100 parts by weight of methanol, stirred at room temperature for 24 hours, and centrifuged at 8000r / min×5min to obtain a zinc-based zeolite imidazole ester framework; under stirring conditions, 0.5 parts by weight of the above-synthesized zinc-based zeolite imidazole ester framework is added to 100 parts by weight of anhydrous methanol containing 3 parts by weight of cobalt nitrate hexahydrate and 3 parts by weight of nickel nitrate hexahydrate, and stirred at room temperature for 1 hour. , obtaining a zinc-based zeolite imidazolate skeleton modified with cobalt and nickel ions; then adding 100 parts by weight of methanol containing 6 parts by weight of 2-methylimidazole, centrifuging and washing at 8000r / min×5min to obtain a cobalt-nickel-zinc-based zeolite imidazolate skeleton; drying the synthesized cobalt-nickel-zinc-based zeolite imidazolate skeleton under a vacuum environment of 80 degrees Celsius, placing it in a tubular furnace protected by a nitrogen atmosphere, heating it to 800 degrees at a heating rate of 2 degrees Celsius per minute for carbonization for 2 hours to obtain a hollow cobalt-nickel-carbon nanocage;
[0014] 2) Preparation of few-layer MXene solution
[0015] Dissolve 1 part by weight of LiF in 20 parts by weight of 9M hydrochloric acid, then add 1 part by weight of Ti3AlC2 powder and stir for 48 hours; the suspension obtained after the reaction is centrifuged at 3500r / min×5min, washed with deionized water until the supernatant PH ≥5, and pour out the supernatant; disperse the obtained precipitate into 25 parts by weight of deionized water, ultrasonicate in an ice bath for 1h, then at 3500r / min×60min, collect the supernatant to obtain a few-layer MXene solution; freeze the few-layer MXene solution in a -4°C refrigerator, and then freeze-dry it in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a few-layer MXene powder;
[0016] 3) Preparation of double-layer electromagnetic shielding aerogel
[0017] Under ultrasonic and stirring conditions, the few-layer MXene powder obtained in the above step 2) is dispersed into a 1% by weight aqueous solution of cellulose nanofibers at a weight ratio of 0.1:1 to 1:1, preferably 0.25:1 to 0.75:1, and more preferably 0.5:1 to the cellulose nanofibers, and then placed in a container and frozen at -4°C; the hollow cobalt-nickel-carbon nanocage obtained in the above step 1) is dispersed into a 1% by weight aqueous solution of cellulose nanofibers at a weight ratio of 0.1:1 to 1:1, preferably 0.25:1 to 0.75:1, and more preferably 0.5:1 to the cellulose nanofibers, and then poured onto the frozen few-layer MXene / cellulose nanofibers, the volume ratio of the two solutions is 1:1, and then frozen again at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0018] According to another aspect of the present invention, another object of the present invention is to provide use of the electromagnetic shielding aerogel with a double-layer structure in electromagnetic stealth devices and electronic equipment resistant to harsh environments.
[0019] Beneficial Effects
[0020] 1. The preparation method of the electromagnetic shielding aerogel prepared according to the present invention is simple and has a wide range of applications;
[0021] 2. The electromagnetic shielding aerogel prepared according to the present invention has the characteristics of low density and good stability;
[0022] 3. The electromagnetic shielding aerogel prepared according to the present invention has excellent low-reflection characteristics and gigahertz electromagnetic shielding performance;
[0023] 4. The electromagnetic shielding aerogel prepared according to the present invention shows good results in actual simulated electromagnetic shielding tests, and has the possibility of adjustable size and large-scale production;
[0024] 5. The key point of the present invention is that the electromagnetic shielding aerogel has a double-layer structure, which brings the above-mentioned good electromagnetic stealth effect. The double-layer structure can cause the incident electromagnetic wave to be scattered and reflected multiple times between the absorption layer and the reflection layer. The absorption layer plays a role in extending the propagation path of the electromagnetic wave and reducing the reflection. The reflection layer plays a role in blocking the electromagnetic wave and enhancing the electromagnetic wave shielding ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 The figure is a flow chart of the preparation of electromagnetic shielding aerogel according to the present invention.
[0027] Figure 2 X-ray diffraction patterns of the first and second layers of the electromagnetic shielding aerogel prepared according to Example 1, cellulose nanofibers, few-layer MXene, and hollow cobalt-nickel-carbon nanocages.
[0028] Figure 3 Transmission electron microscopy images of hollow cobalt-nickel-carbon nanocages, few-layer MXene and cellulose nanofibers prepared according to Example 1.
[0029] Figure 4 The Raman spectra of the few-layer MXene, cobalt-nickel-zinc-based zeolite imidazolate framework and hollow cobalt-nickel-carbon nanocage prepared according to Example 1.
[0030] Figure 5 The gas adsorption-desorption curves, specific surface areas and corresponding pore size distribution diagrams of the cobalt-nickel-zinc-based zeolite imidazolate framework and hollow cobalt-nickel-carbon nanocage prepared according to Example 1 are shown.
[0031] Figure 6 This is a transmission electron microscope energy spectrum diagram of the hollow cobalt-nickel-carbon nanocage prepared according to Example 1.
[0032] Figure 7 This is a scanning electron microscope image of the electromagnetic shielding aerogel prepared according to Example 1.
[0033] Figure 8 Optical photographs of the electromagnetic shielding aerogels prepared according to Example 1 and Comparative Examples 1-2.
[0034] Fig. 9 This is a test of the electromagnetic shielding performance of the electromagnetic shielding aerogels prepared according to Examples 1-7 and Comparative Examples 1-3.
[0035] Fig.10 This is a test of the electromagnetic stealth correlation coefficient of the electromagnetic shielding aerogel prepared according to Examples 1-7 and Comparative Examples 1-3.
[0036] Fig.11 This is a test of the electromagnetic shielding performance of the electromagnetic shielding aerogels prepared according to Example 1 and Comparative Example 3.
[0037] Fig.12 This is an application test of the electromagnetic shielding aerogel according to Example 1 to simulate the actual electromagnetic shielding performance.
[0038] Fig.13 This is a lightweight characteristic picture of the electromagnetic shielding aerogel prepared according to Example 1. DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.
[0040] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed in this document, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".
[0041] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.
[0042] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0043] The electromagnetic shielding aerogel with a double-layer structure prepared according to the preparation method of the present invention not only has excellent low-reflection characteristics of gigahertz electromagnetic shielding performance, but also has unique double-sided heterogeneous photothermal conversion performance. Figure 1 The figure is a flow chart for preparing the electromagnetic shielding aerogel according to the present invention.
[0044] In the preparation method according to the present invention, the weight ratio of the few-layer MXene to the hollow cobalt nickel carbon nanocage is 0.1:1 to 10:1, more preferably 0.3:1 to 3:1, and more preferably 1:1. When the weight ratio of the few-layer MXene to the hollow cobalt nickel carbon nanocage is greater than 3:1, the electromagnetic stealth capability of the electromagnetic shielding aerogel will decrease. When the weight ratio of the few-layer MXene to the hollow cobalt nickel carbon nanocage is less than 0.3:1, the electromagnetic shielding capability of the electromagnetic shielding aerogel will decrease.
[0045] In the preparation method according to the present invention, the weight ratio of the few-layer MXene powder to the cellulose nanofiber is 0.1:1 to 1:1; preferably 0.25:1 to 0.75:1, and more preferably 0.5:1. When the weight ratio of the few-layer MXene to the cellulose nanofiber is greater than 0.75:1, the magnetism of the electromagnetic shielding aerogel is insufficient. When the weight ratio of the few-layer MXene to the cellulose nanofiber is less than 0.25:1, the conductivity of the electromagnetic shielding aerogel is insufficient.
[0046] In the preparation method according to the present invention, the weight ratio of the hollow cobalt nickel carbon nanocage to the cellulose nanofiber is 0.1:1 to 1:1; preferably 0.25:1 to 0.75:1, and more preferably 0.5:1. When the weight ratio of the hollow cobalt nickel carbon nanocage to the cellulose nanofiber is greater than 0.75:1, the conductivity of the electromagnetic shielding aerogel is insufficient. When the weight ratio of the few-layer MXene to the hollow cobalt nickel carbon nanocage is less than 0.25:1, the magnetism of the electromagnetic shielding aerogel is insufficient.
[0047] The cellulose nanofibers used in the preparation method according to the present invention are not particularly limited and can be commercially available products, such as the cellulose nanofiber product model TOCNF-PL-2 purchased from Tianjin Wood Elf Technology Co., Ltd.
[0048] According to the preparation method of the present invention, the double-layer electromagnetic shielding aerogel has a double-layer structure. When the electromagnetic shielding aerogel does not have a double-layer structure, the mutual penetration between the electromagnetic components and the non-conductive components in the electromagnetic shielding aerogel becomes serious, resulting in a decrease in electromagnetic shielding capability.
[0049] Specifically, according to the double-layer electromagnetic shielding aerogel, the preparation method of the double-layer electromagnetic shielding aerogel, step 1) preparing hollow cobalt-nickel-carbon nanocages and step 2) preparing a few-layer MXene solution are both conventional preparation methods and are not limited to the method defined in the invention content section of the present disclosure.
[0050] Electromagnetic shielding performance is usually determined by factors such as magnetic loss and electric loss capacity, electric dipoles and magnetic dipoles, and multiple interfaces. Magnetic loss and electric loss capacity are crucial aspects. They can greatly affect the effectiveness of electromagnetic shielding by absorbing and consuming electromagnetic energy. The existence of electric dipoles and magnetic dipoles and their related characteristics also play an indispensable role in the electromagnetic shielding process. Their distribution and state will have a significant impact on the shielding performance. Furthermore, the factor of multiple interfaces should not be underestimated. The unique characteristics of the interface formed between different media will change the propagation path and reflection of the electromagnetic field, thereby further having an important impact on the overall electromagnetic shielding performance. Few-layer MXene and hollow cobalt-nickel-carbon nanocages have strong electric loss and magnetic loss capacity. The double-layer design distribution of asymmetric charge distribution will lead to the polarization of electric / magnetic dipoles, forming interacting dipoles and generating multiple interfaces.
[0051] The electromagnetic shielding aerogel prepared according to the preparation method of the present invention has an excellent electromagnetic shielding performance with low reflection characteristics. Under the premise of a reflection coefficient of 0.28, its electromagnetic shielding capability in the gigahertz range can reach 35.1dB. Under the premise of a reflection coefficient of 0.25, its electromagnetic shielding capability in the gigahertz range can reach 21.2dB.
[0052] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.
[0053] Example 1
[0054] 1) Preparation of hollow cobalt-nickel-carbon nanocages
[0055] Under stirring conditions, 6 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added to 100 g of methanol, stirred at room temperature for 24 hours, and centrifuged at 8000 r / min×5 min to obtain a zinc-based zeolite imidazole ester framework; under stirring conditions, 0.5 g of the above-synthesized zinc-based zeolite imidazole ester framework was added to 100 g of anhydrous methanol containing 3 g of cobalt nitrate hexahydrate and 3 g of nickel nitrate hexahydrate, stirred at room temperature for 1 hour, and a zinc-based zeolite imidazole ester framework modified with cobalt and nickel ions was obtained; and then 6 g of 100 g of 2-methylimidazole was dissolved in methanol, and centrifuged at 8000 r / min×5 min to obtain a cobalt-nickel-zinc-based zeolite imidazole ester framework; the cobalt-nickel-zinc-based zeolite imidazole ester framework synthesized above was dried under a vacuum environment of 80 degrees Celsius, placed in a tubular furnace protected by a nitrogen atmosphere, and heated to 800 degrees at a heating rate of 2 degrees Celsius per minute for carbonization for 2 hours to obtain a hollow cobalt-nickel-carbon nanocage;
[0056] 2) Preparation of few-layer MXene solution
[0057] Dissolve 1g LiF in 20g 9M hydrochloric acid, then add 1g Ti3AlC2 powder and stir for 48h; the suspension obtained after the reaction is centrifuged at 3500r / min×5min, washed with deionized water until the supernatant PH ≥ 5, and pour out the supernatant; disperse the obtained precipitate into 25g deionized water, ultrasonicate in an ice bath for 1h, then at 3500r / min×60min, collect the supernatant to obtain a few-layer MXene solution; freeze the few-layer MXene solution in a -4℃ refrigerator, and then freeze-dry it in a vacuum freeze dryer at -48℃ and a vacuum degree of 20Pa to obtain a few-layer MXene powder;
[0058] 3) Preparation of double-layer electromagnetic shielding aerogel
[0059] Under ultrasonic and stirring conditions, the few-layer MXene powder obtained in the above step 2) is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:2 to the cellulose nanofiber, and then 300 mL is placed in a container and frozen at -4°C. The hollow cobalt-nickel-carbon nanocage obtained in the above step 1) is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:2 to the cellulose nanofiber, and then 300 mL is poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen again at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel, wherein the weight ratio of the few-layer MXene to the hollow cobalt-nickel-carbon nanocage is 1:1.
[0060] like Figure 2As shown, the electromagnetic shielding aerogel prepared in Example 1 was analyzed using an X-ray diffraction spectrum, and it can be seen that the diffraction peaks of the various components of the first layer and the second layer of the electromagnetic shielding aerogel are obvious, proving the successful preparation of the composite material and the successful construction of the double-layer structure.
[0061] like Figure 3 As shown, the hollow cobalt-nickel-carbon nanocages, few-layer MXene and cellulose nanofibers prepared in Example 1 were characterized by transmission electron microscopy, which further proved the successful synthesis of the raw materials.
[0062] like Figure 4 As shown, Raman spectroscopy characterization tests were performed on the few-layer MXene, cobalt-nickel-zinc-based zeolite imidazolate framework and hollow cobalt-nickel-carbon nanocage prepared in Example 1. It can be seen that after carbonization, the cobalt-nickel-zinc-based zeolite imidazolate framework is transformed into a hollow cobalt-nickel-carbon nanocage with a high degree of graphitization.
[0063] like Figure 5 As shown, the cobalt-nickel-zinc-based zeolite imidazole ester framework and the hollow cobalt-nickel-carbon nanocage prepared in Example 1 were analyzed using a fully automatic specific surface area and porosity analyzer, proving the successful construction of the hollow structure of the material.
[0064] like Figure 6 As shown, the hollow cobalt-nickel-carbon nanocage prepared in Example 1 was analyzed by energy spectrum analysis, which further proved the element distribution in its structure.
[0065] like Figure 7 As shown, the electromagnetic shielding aerogel prepared in Example 1 was tested by scanning electron microscopy, which proved its porous structure and the different properties of the double-layer structure.
[0066] Fig.13 The electromagnetic shielding aerogel according to Example 1 can be easily held up by the dandelion hairs without bending, indicating that the electromagnetic shielding aerogel has the characteristics of being lightweight. The density is 31.2 mg / cm 3 .
[0067] Example 2
[0068] Except that the weight ratio of the few-layer MXene and the hollow cobalt-nickel-carbon nanocage in the double-layer electromagnetic shielding aerogel is regulated to be 1:3, the rest of the preparation steps are the same as those in Example 1 to prepare the electromagnetic shielding aerogel (BZMN-5-1:3). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:4 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt-nickel-carbon nanocage is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 3:4 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen again at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0069] Example 3
[0070] Except that the content ratio of the few-layer MXene and the hollow cobalt-nickel-carbon nanocage in the double-layer electromagnetic shielding aerogel is regulated to 3:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-5-3:1). Specifically as follows: Under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 3:4 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt-nickel-carbon nanocage is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:4 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen again at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0071] Example 4
[0072] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer electromagnetic shielding aerogel is regulated to 0.1:1, and the content ratio of the hollow cobalt nickel carbon nanocage and cellulose nanofibers is regulated to 0.1:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-1-1:1). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.1:1 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt nickel carbon nanocage is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.1:1 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0073] Example 5
[0074] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer electromagnetic shielding aerogel is regulated to 0.2:1, and the content ratio of the hollow cobalt nickel carbon nanocage and cellulose nanofibers is regulated to 0.2:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-2-1:1). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.2:1 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt nickel carbon nanocage is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.2:1 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0075] Example 6
[0076] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer electromagnetic shielding aerogel is regulated to 0.3:1, and the content ratio of the hollow cobalt nickel carbon nanocage and cellulose nanofibers is regulated to 0.3:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-3-1:1). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.3:1 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt nickel carbon nanocage is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.3:1 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0077] Example 7
[0078] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer electromagnetic shielding aerogel is regulated to 0.4:1, and the content ratio of the hollow cobalt nickel carbon nanocage and cellulose nanofibers is regulated to 0.4:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-4-1:1). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.4:1 to the cellulose nanofiber, and then placed in a container and frozen at -4°C. The hollow cobalt nickel carbon nanocage is dispersed into a 1% cellulose nanofiber aqueous solution at a weight ratio of 0.4:1 to the cellulose nanofiber, and then poured onto the frozen few-layer MXene / cellulose nanofiber, the volume ratio of the two solutions is 1:1, and then frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0079] Comparative Example 1
[0080] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer structure electromagnetic shielding aerogel is regulated to be 1:1, and the content ratio of the hollow cobalt nickel carbon nanocage and the cellulose nanofiber is regulated to be 0:1, that is, it does not contain hollow cobalt nickel carbon nanocages, the rest is prepared according to the same preparation steps as Example 1 to obtain an electromagnetic shielding aerogel (BZMN-5-1:0). Specifically as follows: Under ultrasonic and stirring conditions, the few-layer MXene powder is dispersed into a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:1 with the cellulose nanofiber, and then placed in a container and frozen at -4°C. Then pour the same volume of 1% by weight cellulose nanofiber aqueous solution, and then freeze it again at -4°C, and then freeze-dry it in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer structure electromagnetic shielding aerogel.
[0081] Comparative Example 1
[0082] Except that the content ratio of the few-layer MXene and cellulose nanofibers in the double-layer electromagnetic shielding aerogel is regulated to 0:1, that is, it does not contain few-layer MXene, and the content ratio of the hollow cobalt nickel carbon nanocage and the cellulose nanofiber is regulated to 1:1, the rest is prepared according to the same preparation steps as in Example 1 to obtain an electromagnetic shielding aerogel (BZMN-5-0:1). Specifically, a 1% by weight cellulose nanofiber aqueous solution is placed in a container and frozen at -4°C. Under ultrasonic and stirring conditions, the hollow cobalt nickel carbon nanocage is dispersed in a 1% by weight cellulose nanofiber aqueous solution at a weight ratio of 1:1 to the cellulose nanofiber, and then the same volume is poured onto the frozen cellulose nanofiber frozen liquid, and then frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
[0083] Comparative Example 3
[0084] The dosage of the few-layer MXene and hollow cobalt-nickel carbon nanocage, and cellulose nanofiber aqueous solution is the same as that in Example 1, but the MXene and hollow cobalt-nickel carbon nanocage cellulose nanofiber aqueous solution are directly mixed without stratification, and the rest is prepared according to the same preparation steps as in Example 1 to obtain electromagnetic shielding aerogel (RZMN-5-1:1). Specifically, under ultrasonic and stirring conditions, the few-layer MXene powder, hollow cobalt-nickel carbon nanocage and 1% by weight cellulose nanofiber solution are evenly dispersed according to the weight ratio of MXene powder, hollow cobalt-nickel carbon nanocage and cellulose nanofiber of 1:1:2, and then placed in a container and frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain an electromagnetic shielding aerogel with a random mixed structure.
[0085] Table 1. Solid content of sample components in Examples and Comparative Examples
[0086]
[0087] like Figure 8 As shown, from left to right, the first layer and the second layer of the electromagnetic shielding aerogel prepared in Example 1 and Comparative Examples 1-2 are shown, and the colors are clearly distinguished, proving the successful construction of the electromagnetic shielding aerogel double-layer structure.
[0088] Experimental Example 1: Gigahertz Electromagnetic Shielding Experiment
[0089] The electromagnetic shielding aerogels prepared in Examples 1-7 and Comparative Examples 1-3 were cut into sizes suitable for the waveguide cavity of a vector network analyzer and then fixed in the waveguide cavity of the vector network analyzer. Under electromagnetic wave radiation with a frequency of 8.2-12.4 GHz, the S parameters before and after the electromagnetic wave transmission were measured, and the electromagnetic shielding energy efficiency was calculated from the S parameters.
[0090] Fig. 9 The electromagnetic shielding performance test was carried out on the electromagnetic shielding aerogels prepared in Examples 1-7 and Comparative Examples 1-3. The test results showed that the electromagnetic shielding efficiency of the aerogel in Example 1 was greater than 20 dB, and it was able to shield more than 99% of electromagnetic wave radiation, proving that it had good electromagnetic shielding performance.
[0091] Fig.10 The electromagnetic shielding aerogels prepared for Examples 1-7 and Comparative Examples 1-3 were tested for electromagnetic stealth performance. The test results showed that the aerogel absorption coefficient of Example 1 was as high as 0.75, and it was able to hide more than 75% of electromagnetic wave radiation, proving that it had good electromagnetic stealth performance.
[0092] Fig.11 The electromagnetic shielding energy efficiency test results of the electromagnetic shielding aerogels prepared in Example 1 and Comparative Example 3 show that the double-layer structure can give the electromagnetic shielding aerogel more excellent shielding performance, and Example 1 has the best electromagnetic shielding performance with low reflection characteristics.
[0093] Experimental Example 2: Actual Electromagnetic Shielding Simulation
[0094] The electromagnetic shielding aerogel prepared in Example 1 was placed between a running electronic device and an electromagnetic radiation detector, and the value changes of the electromagnetic radiation instrument were observed to test the electromagnetic shielding ability of the electromagnetic shielding aerogel.
[0095] Fig.12The figure is a simulation test diagram of the actual electromagnetic shielding of the electromagnetic shielding aerogel prepared in Example 1 and the corresponding value change diagram. When the electromagnetic shielding aerogel is not placed, the value of the electromagnetic radiation detector increases and the alarm light is on. When the electromagnetic shielding aerogel is placed, the value of the electromagnetic radiation detector decreases and the alarm light goes out. The figure shows that the electromagnetic shielding aerogel prepared in Example 1 has good shielding performance against electromagnetic waves, and the radiation intensity after shielding is within the safety threshold specified by the International Commission on Non-Ionizing Radiation Protection.
[0096] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An electromagnetic shielding aerogel with a double-layer structure, which is composed of cellulose nanofibers, hollow cobalt-nickel-carbon nanocages and a few-layer MXene. The electromagnetic shielding aerogel has a double-layer structure, the first layer is composed of cellulose nanofibers and hollow cobalt-nickel-carbon nanocages, and the second layer is composed of cellulose nanofibers and a few-layer MXene.
2. The electromagnetic shielding aerogel with a double-layer structure according to claim 1, characterized in that: The electromagnetic shielding aerogel with a double-layer structure according to claim 1 is characterized in that the weight content of the hollow cobalt-nickel-carbon nanocage in the first layer and the few-layer MXene in the second layer in the electromagnetic shielding aerogel is the same or different, and preferably the content of the two is the same.
3. The electromagnetic shielding aerogel with a double-layer structure according to claim 1, characterized in that: The electromagnetic shielding aerogel has the same cellulose nanofiber content in the first layer and the second layer.
4. The electromagnetic shielding aerogel with a double-layer structure according to claim 1, characterized in that: In the electromagnetic shielding aerogel, the weight ratio of the few-layer MXene to the hollow cobalt-nickel-carbon nanocage is 0.1:1 to 10:1, more preferably 0.3:1 to 3:1, and even more preferably 1:
1.
5. The electromagnetic shielding aerogel with a double-layer structure according to claim 1, characterized in that: The weight ratio of the few-layer MXene powder to the cellulose nanofibers is 0.1:1 to 1:1; preferably 0.25:1 to 0.75:1, and more preferably 0.5:
1.
6. The electromagnetic shielding aerogel with a double-layer structure according to claim 1, characterized in that: The weight ratio of the hollow cobalt-nickel-carbon nanocage to the cellulose nanofiber is 0.1:1 to 1:1, preferably 0.25:1 to 0.75:1, and more preferably 0.5:
1.
7. The method for preparing the electromagnetic shielding aerogel having a double-layer structure according to any one of claims 1 to 6, comprising the following steps: 1) Preparation of hollow cobalt-nickel-carbon nanocages Under stirring conditions, 6 parts by weight of zinc nitrate hexahydrate and 6 parts by weight of 2-methylimidazole are added to 100 parts by weight of methanol, stirred at room temperature for 24 hours, and centrifuged at 8000r / min×5min to obtain a zinc-based zeolite imidazole ester framework; under stirring conditions, 0.5 parts by weight of the above-synthesized zinc-based zeolite imidazole ester framework is added to 100 parts by weight of anhydrous methanol containing 3 parts by weight of cobalt nitrate hexahydrate and 3 parts by weight of nickel nitrate hexahydrate, and stirred at room temperature for 1 hour. , obtaining a zinc-based zeolite imidazolate skeleton modified with cobalt and nickel ions; then adding 100 parts by weight of methanol containing 6 parts by weight of 2-methylimidazole, centrifuging and washing at 8000r / min×5min to obtain a cobalt-nickel-zinc-based zeolite imidazolate skeleton; drying the synthesized cobalt-nickel-zinc-based zeolite imidazolate skeleton under a vacuum environment of 80 degrees Celsius, placing it in a tubular furnace protected by a nitrogen atmosphere, heating it to 800 degrees at a heating rate of 2 degrees Celsius per minute for carbonization for 2 hours to obtain a hollow cobalt-nickel-carbon nanocage; 2) Preparation of few-layer MXene solution Dissolve 1 part by weight of LiF in 20 parts by weight of 9M hydrochloric acid, then add 1 part by weight of Ti3AlC2 powder and stir for 48 hours; the suspension obtained after the reaction is centrifuged at 3500r / min×5min, washed with deionized water until the supernatant PH ≥5, and pour out the supernatant; disperse the obtained precipitate into 25 parts by weight of deionized water, ultrasonicate in an ice bath for 1h, then at 3500r / min×60min, collect the supernatant to obtain a few-layer MXene solution; freeze the few-layer MXene solution in a -4°C refrigerator, and then freeze-dry it in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a few-layer MXene powder; 3) Preparation of double-layer electromagnetic shielding aerogel Under ultrasonic and stirring conditions, the few-layer MXene powder obtained in the above step 2) is dispersed into a 1% by weight aqueous solution of cellulose nanofibers at a weight ratio of 0.1:1 to 1:1, preferably 0.25:1 to 0.75:1, and more preferably 0.5:1 to the cellulose nanofibers, and then placed in a container and frozen at -4°C; the hollow cobalt-nickel-carbon nanocage obtained in the above step 1) is dispersed into a 1% by weight aqueous solution of cellulose nanofibers at a weight ratio of 0.1:1 to 1:1, preferably 0.25:1 to 0.75:1, and more preferably 0.5:1 to the cellulose nanofibers, and then poured onto the frozen few-layer MXene / cellulose nanofibers, the volume ratio of the two solutions is 1:1, and then frozen again at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain a double-layer electromagnetic shielding aerogel.
8. Use of the electromagnetic shielding aerogel with a double-layer structure according to any one of claims 1 to 6 in electromagnetic stealth devices and electronic equipment resistant to harsh environments.
Citation Information
Patent Citations
Preparation method of MXene / cellulose composite aerogel
CN109679146A
Cellulose nanofiber-assisted nitrogen-doped carbon nanocage flexible film and preparation method thereof
CN110885074A
Preparation method of N, S co-doped MXene / cellulose derived carbon aerogel
CN114804108A
Super-elastic ultra-light regular porous composite aerogel as well as preparation method and application thereof
CN117247594A
Cited By
Flexible low-reflection type electromagnetic shielding composite film and preparation method thereof
CN122278003A
A biomass aerogel prepared by phase separation-assisted atmospheric pressure drying and its application in electromagnetic shielding
CN122668428A